An introduction to the New Testament - Brown, Raymond E. (Raymond Edward), 1928-1998; Soards, Marion L., 1952- (New Haven Yale university press, 1997)
"Since its publication in 1997, Raymond Brown's Introduction to the New Testament has been widely embraced by modern readers seeking to understand the Christian Bible. Acknowledged as a paragon of New Testament studies in his lifetime, Brown was a gifted communicator who wrote with ease and clarity. Abridged by Marion Soards, who worked with Brown on the original text, this new, concise version maintains the essence and centrist interpretation of the original without tampering with Brown's perspective, insights, or conclusions. The biblical writings themselves remain the focus, but there are also chapters dealing with the nature, origin, and interpretation of the New Testament texts, as well as chapters concerning the political, social, religious, and philosophical world of antiquity. Furthermore, augmenting Brown's commentary on the New Testament itself are topics such as the Gospels' relationship to one another; the form and function of ancient letters; Paul's thought and life, along with his motivation, legacy, and theology; a reflection on the historical Jesus; and a survey of relevant Jewish and Christian writings." -- Publisher's description
The Nature and Origin of the New Testament -- How to Read the New Testament -- The Text of the New Testament -- The Political and Social World of New Testament Times -- The Religious and Philosophical World of New Testament Times -- Gospel in General; Synoptic Gospels in Particular -- The Gospel According to Mark -- The Gospel According to Matthew -- The Gospel According to Luke -- The Acts of the Apostles -- The Gospel According to John -- First Epistle (Letter) of John -- Second Letter of John -- Third Letter of John -- Classification and Format of New Testament Letters -- General Issues in Paul's Life and Thought -- An Appreciation of Paul -- First Letter to the Thessalonians -- Letter to the Galatians -- Letter to the Philippians -- Letter to Philemon -- First Letter to the Corinthians -- Second Letter to the Corinthians -- Letter to the Romans -- Pseudonymity and the Deutero-Pauline Writings -- Second Letter to the Thessalonians -- Letter to the Colossians -- Epistle (Letter) to the Ephesians -- Pastoral Letter: to Titus -- Pastoral Letter: the First to Timothy -- Pastoral Letter: the Second to Timothy -- Letter (Epistle) to the Hebrews -- First Letter of Peter -- Epislte (Letter) of James -- Letter (Epistle) of Jude -- Second Epistle (Letter) of Peter -- The Book of Revelation (The Apocalypse).
Includes bibliographical references and index.
Keywords: Bible. -- Introductions; Bible. -- Theology; Bible. -- Canon